2022
DOI: 10.37394/232012.2022.17.13
|View full text |Cite
|
Sign up to set email alerts
|

The Bin Method to Investigate the Effect of Climate Conditions on the SCOP of Air Source Heat Pumps: the Italian Case

Abstract: The paper investigates the seasonal performances of electric air-to-water heat pumps specifically related to climatic conditions of the place where the heat pump is installed. The analysis is carried out using easily available weather data for some Italian towns differently located, and using the bin-method proposed by UNI/TS 11300-4. Two different types of heat pumps (on-off and inverter-driven variable speed compressor) are considered and comparisons between different types of heat pumps and different places… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Moreover, Beccali et al [8] remarked that climate can influence the performance of a heat pump. As demonstrated by many researchers [10][11][12], the climatic and installation conditions affect the entire system's performance. Carrol et al [10] found three main areas of focus within this framework: defrosting management, ASHP system management and ASHPs as smart grid demand response components.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Beccali et al [8] remarked that climate can influence the performance of a heat pump. As demonstrated by many researchers [10][11][12], the climatic and installation conditions affect the entire system's performance. Carrol et al [10] found three main areas of focus within this framework: defrosting management, ASHP system management and ASHPs as smart grid demand response components.…”
Section: Introductionmentioning
confidence: 99%